Understanding Generation Z: Work-Life Balance and Job Embeddedness in Retention Dynamics - Sherly Rosalina Tanoto; Erin Go Tami (Binus Business Review, 2024)
The Great Resignation has presented a significant challenge for companies aiming to retain top talent and emphasize the critical need for effective employee retention strategies. The research investigated the relationship between work-life balance, employee retention, and turnover intention among Generation Z employees across various industries in Indonesia. By encompassing multiple sectors such as technology, finance, healthcare, and hospitality, the research aimed to capture Generation Z employees’ diverse experiences and perceptions. The research involved 373 Generation Z respondents across various industries, employing a quantitative approach. Data collection was facilitated through online questionnaires, and analysis was conducted using Structural Equation Modeling (SEM) with Partial Least Square (PLS) as the analytical tool. The findings reveal significant relationships between various constructs. Work-life balance influences employee retention, turnover intention, and job embeddedness. Additionally, job embeddedness exerts an impact on both employee retention and turnover intention. Furthermore, work-life balance indirectly affects employee retention and turnover intention through its mediation by job embeddedness. The inclusion of diverse industries ensures that the results are broadly applicable, offering practical recommendations for fostering a resilient and engaged workforce in different professional environments. Future research should continue to explore industry-specific nuances to further enrich the understanding of these critical issues.